Multilevel Analysis on Factors Associated with Occurrence Chronic Energy Deficiency among Pregnant Women - Rachmawati, Nur Cahya; Dewi, Yulia Lanti Retno; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2019)
Background: One of the nutritional problems experienced by pregnant women is chronic energy deficiency (CED). Chronic energy deficiency is a condition in which women of childbearing age  experience a lack of energy and protein intake and take place continuously resulting in health problems. This study aims to analyze chronic energy deficiency factors in pregnant women in Gunungkidul Regency.Subjects and Method: This study implemented a case control design. It was conducted in 25 community health centers, Gunungkidul, Yogyakarta, from April to May 2019. A sample of 200 pregnant women was selected by fixed disease sampling. The dependent variable was chronic energy deficiency in pregnant women. The independent variables included food intake, education level, occupation, knowledge, family income, age, parity, utilization of antenatal care services (ANC), and food availability. The data were collected using the MUAC tape and questionnaire. The data were analyzed by a multilevel multiple logistic regression.Results: The risk of protein energy deficiency decreased with high energy and protein intake (b = -2.74; 95% CI = -7.74 to -1.28; p = 0.006), more education level than high school (b = -2.16; 95% CI = -4.54 up to -0.22; p = 0.030), working mothers (b = -2.75; CI 95% = -9.48 to -1.59; p = 0.006), sufficient knowledge (b = -2.32; CI 95% = -6.27 to -0.52; p = 0.020), high family income (b = -2.38; CI 95% = -6.27 to -0.60; p = 0.017), age ?20 years to 35 years (b = -2.17; 95% CI = -5.16 to - 0.26; p = 0.030), parity> 2 (b = -2.57; CI 95% = -8.42 to -1.13; p = 0.010), using high ANC services (b = -2.72; 95% CI = -9.20 to -1.49 ; p = 0.007), and food availability is fulfilled (b = -2.54; CI 95% = -7.63 to -0.98; p = 0.011). Public health centers had a large contextual influence on chronic energy shortages with an ICC of 51.25%.Conclusion: There is a significant influence between food intake, education level, occupation, knowledge, family income, age, parity, utilization of ANC services, and food availability for chronic energy shortages in pregnant women. The variations at the public health centers level show that there is a contextual influence on chronic energy shortages in pregnant women.Keywords: chronic energy deficiency (CED), multilevel analysis, pregnant womenCorrespondence: Nur Cahya Rachmawati. Master?s Program in Public Health, Universitas Sebelas Maret, Surakarta, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: nurcahyarachmawatii@gmail.com. Mobile: +6287838992205.Journal of Maternal and Child Health (2019), 4(6): 474-485https://doi.org/10.26911/thejmch.2019.04.06.08